Characterizing the providers of and reimbursement for chronic migraine chemodenervation among the Medicare population. Issue 2 (18th December 2020) - Torabi, Sina J.; Kasle, David A.; Savoca, Emily L.; Gottschalk, Christopher H.; Manes, R. Peter
Abstract: Objective: To characterize reimbursement trends and providers for chronic migraine (CM) chemodenervation treatment within the Medicare population since the introduction of the migraine‐specific CPT code in 2013. Methods: We describe trends in procedure volume and total allowed charge on cross‐sectional data obtained from 2013 to 2018 Medicare Part B National Summary files. We also utilized the 2017 Medicare Provider Utilization and Payment Data to analyze higher volume providers (>10 procedures) of this treatment modality. Results: The total number of CM chemodenervation treatments rose from 37, 863 in 2013 to 135, 023 in 2018 in a near‐linear pattern ( r = 0.999) and total allowed charges rose from 5, 217, 712 to 19, 166, 160 ( r = 0.999). The majority of high‐volume providers were neurologists (78.4%; 1060 of 1352), but a substantial proportion were advanced practice providers (APPs) (10.2%; 138 of 1352). Of the physicians, neurologists performed a higher mean number of procedures per physician compared to non‐neurologists (59.6 [95% CI: 56.6–62.6] vs. 45.4 [95% CI: 41.0–50.0], p < 0.001). When comparing physicians and APPs, APPs were paid significantly less (146.5 [95% CI: 145.6–147.5] vs. 119.7 [95% CI: 117.6–121.8], p < 0.001). As a percent of the number of total beneficiaries in each state, the percent of Medicare patients receiving ≥1 CM chemodenervation treatment from a high‐volume provider in 2017 ranged from 0.024% (24 patients of 98, 033 beneficiaries) in Wyoming to 0.135% (997 of 736, 521) in Arizona, with six states falling outside of this range. Conclusion: Chemodenervation is an increasingly popular treatment for CM among neurologists and other providers, but the reason for this increase is unclear. There is substantial geographic variation in its use.